Why We Should Negatively Discount the Well-Being of Future Generations - Matthew Price (Journal of Practical Ethics)
Traditionally, the discounting debate has been dominated by those who advocate equality between generational interests and those who think future generations’ interests should be discounted at some positive rate. This paper argues for a novel view: future generations’ interests should be negatively discounted. First I defend the claim that we have greater reason to promote the well-being of those who are more morally deserving. Then I explain why we should expect future people to be more morally deserving than us. Throughout this argument, scepticism about moral desert looms large. Nevertheless, given the context of moral uncertainty under which the discounting decision must be made, a negative discount rate remains a live option even in the face of a moderate degree of scepticism about moral desert.